The Vikings - Willis, Sam (Willis, Sam., 2019)
Traditionally, the Vikings have been understood in a straightforward way ? but the period really comes alive if you take an unexpected approach to its history. Yes, ships, raiding and trade have a fascinating history... but so too do hair, break-ins, toys, teeth, mischief, luck and silk! --